2016 49th Hawaii International Conference on System Sciences (HICSS) 2016
DOI: 10.1109/hicss.2016.195
|View full text |Cite
|
Sign up to set email alerts
|

Testing Best Practices to Reduce the Overconfidence Bias in Multi-criteria Decision Analysis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Our results show a clear benefit of the MOLE technique for both the calibration and accuracy of elicited ranges. We found little support, however, for the role of initial best guesses or simple counter-intuitive values in improving elicitationsthe latter observation being in line with Ferretti et al's (2016) results.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Our results show a clear benefit of the MOLE technique for both the calibration and accuracy of elicited ranges. We found little support, however, for the role of initial best guesses or simple counter-intuitive values in improving elicitationsthe latter observation being in line with Ferretti et al's (2016) results.…”
Section: Discussionsupporting
confidence: 48%
“…-that can be answered using natural, frequentist reasoning. In fact, while there is evidence that people are better at evaluating than generating ranges (Winman, Hansson, & Juslin, 2004), range evaluation still results in some overconfidence (Winman et al, 2004) and recent work by Ferretti, Guney, Montibeller and von Winterfeldt (2016), found limited benefit in an experiment where participants both generated and then evaluated a range. Given this, overconfidence can not be dismissed.…”
Section: Overconfidencementioning
confidence: 99%
See 1 more Smart Citation
“…local temperature and the Dow Jones), Abbas et al 160 found less evidence of overconfidence using the fixed-value method. However, Ferretti et al 148 found that this resulted in relatively little improvement in performance. Hence, although there is some evidence that fixed-value approaches may reduce overconfidence, this is limited.…”
Section: Fixed Value Compared With Fixed Probability Methodsmentioning
confidence: 99%
“…This is consistent with research suggesting that people may be better at evaluating confidence intervals than providing them. 146,147 More recently, Ferreti et al 148 noted reductions in overconfidence when environmental science students were instructed to (1) actively think of reasons why their initial highest and lowest estimates of sea level rise may be incorrect; and (2) consider their willingness to place hypothetical bets on elicited confidence intervals.…”
Section: Consider More Informationmentioning
confidence: 99%